Experimental toxocariasis in BALB/c mice: relationship between parasite inoculum and the IgG immune response - Fonseca, Gabriela Rodrigues e; Santos, Sergio Vieira dos; Chieffi, Pedro Paulo; Paula, Fabiana Martins de; Gryschek, Ronaldo Cesar Borges; Lescano, Susana Angélica Zevallos (Memórias do Instituto Oswaldo Cruz, 2017)
BALB/c mice were inoculated with 5-500 Toxocara canis infective eggs, and bled at 15-120 days post infection (dpi) to evaluate the dynamics of IgG antibody response and larvae distribution. Positive results were observed in all occasions for every inoculum, and a direct proportional relationship between antibody detection and the parasitic load was observed. In samples collected at 60 dpi, detection of IgG was more intense, especially with the 50 and 500 egg doses; also, a correlation between antibody level and egg count was observed with these two inocula. At 120 dpi, a decrease in antibody titer was observed for all groups; and at the end of the experiment, larvae were recovered from carcass, liver and brain. In the liver, larvae were only found in mice inoculated with 500 T. canis eggs. In carcasses, these were recovered in all groups, and the group inoculated with 50 eggs showed the highest percentage of larvae in the brain.